Implementasi Sustainable Tourism Dalam Pemulihan Citra Pariwisata Bali Pasca Isu “Bali Tak Layak Dikunjungi Tahun 2025” Pada Dinas Pariwisata Provinsi Bali - Esta, Puput Fera Ari; Wirantari, I Dewa Ayu Putri (Lenggogeni Data Publishing, 2025)
This research discusses the implementation of the concept of sustainable tourism as a strategy for the Bali Provincial Tourism Office to restore Bali's tourism reputation after the emergence of the negative issue 'Bali Is Not Worth Visiting in 2025'. This issue has affected tourists' perceptions and reduced public confidence in Bali as a primary tourist destination. Additionally, the concept of Good Governance also plays a significant role in internal government management in the formation of programs that will be realized into the concept of sustainable tourism. Using a descriptive qualitative approach with interview, observation, and documentation methods, this research explains the real steps taken by the government, including strengthening local cultural identity. The Tourism Office strives to balance economic, social, and environmental interests by involving various parties, such as traditional villages, local communities, and the private sector in managing tourist sites. The results of this study indicate that the implementation of sustainable tourism not only has the potential to gradually improve Bali's tourism image but also strengthens Bali's position as a responsible, environmentally friendly, and sustainable global destination. This step also represents a form of change towards a more equitable and fair tourism management that prioritizes the long-term interests of the community and the environment in Bali. Abstrak Penelitian ini membahas implementasi konsep sustainable tourism (pariwisata berkelanjutan) sebagai strategi Dinas Pariwisata Provinsi Bali untuk memulihkan reputasi pariwisata Bali setelah munculnya isu negatif